Analysis of Online Zumba Post Covid-19 Pandemic: Case Study of A Fitness Center in Kemang, South Jakarta - Hernandi, Redidzia; Afandi, Aisyah Arimurti; ., Asfarinal; Nandhito, Garrin Alif (UI Scholars Hub, 2023)
Background: This research discusses the analysis of zumba in the network (online or online) during the Covid-19 pandemic and after the Covid-19 pandemic with the perspective of socio-cultural change. Aims: The aim of this research is to analyze the implementation of online Zumba and its sustainability after the pandemic. Methods: The research method used in this research is literature study and interviews which are then analyzed within the framework of the interactional dimension of socio-cultural change theory. The interactional dimension of socio-cultural change theory is defined as a symptom of changing social structures and cultural patterns in a society. The interactional dimension of socio-cultural change theory has five aspects, namely: changes in frequency, changes in social distance, changes in intermediaries, changes in rules or patterns, and changes in interactions. Results: The results of literature analysis and interviews state that there has been an increase in the frequency of online zumba, adjustments to social distance, changes in intermediaries, changes in rules, and changes in interactions. Conclusion: Online zumba is a new sports business segment that has been maintained after the Covid-19 pandemic with adjustments to become hybrid zumba classes. Hybrid Zumba is carried out by combining members who attend in person and members who attend online. Even though the YouTube platform now has a variety of zumba videos, online zumba is recognized as superior because of the two-way social interaction between instructors and members.